CORPORATE INVESTMENT AND TAX PLANNING DECISIONS: A MARKET EVALUATION - Kamilah, Afifah Nur; Sutrisno, Paulina (Kesatuan Press, 2025)
This study aims to provide empirical evidence on the impact of firm characteristics, such as capital structure, size, profitability, and tax planning, on firm value. It also examines how investment decisions impact the relationship between these characteristics and firm value. Utilizing a sample of consumer cyclical and non-cyclical firms on the Indonesia Stock Exchange from 2019 to 2022, the research offers insights into company conditions and market evaluations amid high uncertainty, particularly during the COVID-19 pandemic. The combination of the two types of industrial sectors in this study will have a more comprehensive impact on the test results. Results indicate that capital structure and profitability positively influence firm value, while firm size and tax planning do not have a significant effect. Moreover, the study reveals that investment decisions shape the relationship between capital structure, firm size, profitability, and firm value. When making assessments, the market evaluates the quality of a firm's funding structure, profit-generating capability, investment decisions, and firm characteristics. This research holds implications for investors, aiding them in making informed investment choices that consider capital structure and profitability, along with strategic investment approaches by management to achieve optimal performance.